Computed tomography with stress maneuvers for diagnosing syndesmotic instability: a summarized research protocol for a new examination - Rodrigues, João; Godoy-Santos , Alexandre; Prado , Marcelo; Alloza , José; Amaral e Castro , Adham; Masagão , Renato; Barros , Durval; Nery , Caio; Rosemberg , Laercio (Journal of the Foot & Ankle, 2020)
Syndesmotic instability is a fundamental question that guides treatment; despite the currently available diagnostic imaging tests, its determination is still challenging. Knowledge of the instability degree assists the physician in the decision-making process regarding surgical or nonsurgical treatments. The authors are currently conducting a prospective diagnostic accuracy study by consecutively selecting individuals aged 18 years and older with an orthopaedic clinical examination indicating suspected acute syndesmotic injury. Magnetic resonance imaging is the reference standard used for evaluating the diagnostic accuracy of 3 computed tomography index tests. These tests include the neutral position and 2 ankle stress maneuvers: external rotation and dorsiflexion. Comparative measurements between the injured syndesmosis and the uninjured contralateral side of the same individual evaluate the tibiofibular relationship and investigate syndesmotic instability. This study aims to describe a summarized research protocol for a new technique using computed tomography with stress maneuvers and to show a didactic example of syndesmotic instability diagnosis. Level of Evidence V; Diagnostic Studies; Expert Opinion.